Participation and yield of a population-based colorectal cancer screening programme in China. Issue 8 (30th October 2018) - Chen, Hongda; Li, Ni; Ren, Jiansong; Feng, Xiaoshuang; Lyu, Zhangyan; Wei, Luopei; Li, Xin; Guo, Lanwei; Zheng, Zhaoxu; Zou, Shuangmei; Zhang, Yueming; Li, Jiang; et al.
Abstract : Objective: Colorectal cancer (CRC) screening has been widely implemented in many countries. However, evidence on participation and diagnostic yield of population-based CRC screening in China is sparse. Design: The analyses were conducted in the context of the Cancer Screening Program in Urban China, which recruited 1 381 561 eligible participants aged 40–69 years from 16 provinces in China from 2012 to 2015. 182 927 participants were evaluated to be high risk for CRC by an established risk score system and were subsequently recommended for colonoscopy. Participation rates and detection of colorectal neoplasms in this programme were reported and their associated factors were explored. Results: 25 593 participants undertook colonoscopy as recommended, with participation rate of 14.0%. High level of education, history of faecal occult blood test, family history of CRC and history of colonic polyp were found to be associated with the participation in colonoscopy screening. Overall, 65 CRC (0.25%), 785 advanced adenomas (3.07%), 2091 non-advanced adenomas (8.17%) and 1107 hyperplastic polyps (4.33%) were detected. Detection rates of colorectal neoplasms increased with age and were higher for men. More advanced neoplasms were diagnosed in the distal colon/rectum (65.2%). Several factors including age, sex, family history of CRC, dietary intake of processed meat and smoking were identified to be associated with the presence of colorectal neoplasms. Conclusion: The diagnostic yield was not optimal using colonoscopy screening in high-risk populations given the relatively low participation rate. Our findings will provide important references for designing effective population-based CRC screening strategies in the future.